Implementation of School-Based Management on Improving the Quality of Learning (Multi-Site Study at Public Junior High School 1 Mojosari and Public Junior High School 2 Mojoanyar, Mojokerto Regency) - Ruslan Affandi; Murtadhlo Murtadhlo; Amrozi Khamidi (IKIP Widya Darma Surabaya, 2026)
Objective: School-Based Management (SBM) grants schools broader authority in managing education. Data from the education report cards reveal that the quality of learning at Public Junior High School 1 Mojosari (63.1) and Public Junior High School 2 Mojoanyar (60.21) remains below the expected standard. This study seeks to analyze the planning, organizing, implementation, and evaluation of school-based management in improving the quality of learning at Public Junior High School 1 Mojosari and Public Junior High School 2 Mojoanyar in Mojokerto Regency. Method: This study uses a qualitative approach with a multi-site study design. Data were collected through in-depth interviews, observation, and document analysis. Results: The implementation of SBM in both schools resulted in different levels of effectiveness. This is influenced by leadership capacity, stakeholder collaboration, use of technology, and support from school resources. SBM is carried out through participatory planning, team formation, learning supervision, and data-based evaluation. The success of SBM is not only determined by the execution of management functions but also by the school's capacity to integrate resources and stakeholders to improve the quality of learning. Novelty: This multi-site study provides a novel comparative insight into how differences in technological readiness and stakeholder collaboration shape divergent learning quality in the implementation of SBM at two public schools in Mojokerto Regency.